A comprehensive dataset of landslide inventory in Pannonian Croatia: Archived and reported dataMendeley Data - Marina Filipović; Iris Bostjančić; Vlatko Gulam; Ivan Markotić (Data in Brief, 2025)
This dataset provides a comprehensive inventory of landslides in Pannonian Croatia, serving as an essential resource for assessing landslide susceptibility, hazard, and risk. Given the lack of a national-level landslide inventory in Croatia, this dataset represents an initial effort to systematically collect and digitize landslide data. Landslide point data were extracted from archived geological maps created at various scales and from publicly reported landslide locations submitted through the online portal “Report a Landslide”, managed by the Croatian Geological Survey. The data are compiled in ESRI shapefile format using ArcMap 10.2.1 software and standardized in the World Geodetic System 1984 (WGS84) coordinate system.This landslide dataset supports spatial analyses such as landslide density mapping, susceptibility mapping, and hazard and risk assessment. It is suitable for reused by geoscientists, urban planners, and civil protection authorities for future research and hazard mitigation. By consolidating historical and publicly reported data, this dataset aims to contribute to the development of a national landslide inventory and improve landslide risk management in Croatia.